Nishab and How to Issue Professional Zakat in Islamic Law - Saprida Saprida; Zuul Fitriani Umari; Zuul Fitriana Umari (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2022)
The purpose of this study was to determine the nishab and how to issue professional zakat in Islamic law. This type of research uses library research. The data collection technique is carried out by the author by identifying themes or discourses from journals, theses from previous research results, the web (internet), or also data taken from other information related to the theme of this research to look for things in the form of notes, newspapers and and so on related to the research focus. The result of the research is that the professional zakat nishab according to the Fatwa of the Indonesian Ulema Council (MUI) is worth 85 grams of gold with the level of income zakat is 2.5%. How to issue professional zakat, namely net expenditure or net zakat, namely issuing zakat from assets that still reach the nisab after deducting it for daily basic needs, both food, housing, debt and other basic needs for the needs of himself, his family and those who are dependents. If the income after deducting basic needs still reaches the nisab, then zakat is obligatory, but if it does not reach the nisab, zakat is not obligatory. Gross expenditure, namely issuing zakat on gross income. That is, zakat income that reaches Translated from Indonesian to English - www.onlinedoctranslator.com Nisab of 85 grams of gold in a year, is issued 2.5% immediately upon receipt before deducting anything.